Diagnóstico de salud bucodental y factores de riesgo en las unidades educativas Mushuk Rimak y el Colegio a distancia de Loja extensión madre Laura Montoya de la Parroquia san Lucas del Cantón Loja año 2013. - Ochoa Ochoa, Karina Cecibel (2013)
The pathologies of the oral cavity is a public health problem, because until now it is not possible its eradication, which are influenced by factors that modify the state of health or disease in the population. The objectives of this research were to diagnose the presented pathologies , the risk factors , and the prevalence of these pathologies, in the students of the schools " MushukRimak " and "The distance high school of Loja, extension Madre Laura Montoya " of the Parish San Lucas of the Loja Canton, the sample was 121 students, to obtain the data a survey was used, which was completed by the students handwritten, and a dental history which recorded the clinical findings, where the dental decay and gingival inflammation are the most prevalent pathologies within the sample , they are influenced by an improper brushing technique and brushing frequency , as well as a limited visit to the dentist. After completing the study it can be concluded that there is a high rate of abnormalities of the oral cavity, which adversely affect the general health of the population, and that undoubtedly affects the person’s own development and the overall community. Thus, it is recommended promotion and oral preventioncampaigns, to the most risky population. Key words: Oral health, cavities, gingival inflammation.